2016
DOI: 10.1007/s00520-016-3504-8
|View full text |Cite
|
Sign up to set email alerts
|

Fear of cancer recurrence and physical well-being among Chinese cancer survivors: the role of conscientiousness, positive reappraisal and hopelessness

Abstract: Conscientiousness confers benefits on FCR and physical well-being through the mechanisms of positive reappraisal and decreased hopelessness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…The interaction between habitual reappraisal and stressful life events was also not significant when predicting self-reported physical health. Previous research has found habitual reappraisal to affect physical health in the context of health-related stressful experiences, such as when managing life-threatening diseases (Liao et al, 2017; Penley et al, 2002), and in older adulthood (Windsor, 2009). It may be that among young adults who are primarily physically healthy, the interaction between habitual reappraisal and stressful life events is less likely to be observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction between habitual reappraisal and stressful life events was also not significant when predicting self-reported physical health. Previous research has found habitual reappraisal to affect physical health in the context of health-related stressful experiences, such as when managing life-threatening diseases (Liao et al, 2017; Penley et al, 2002), and in older adulthood (Windsor, 2009). It may be that among young adults who are primarily physically healthy, the interaction between habitual reappraisal and stressful life events is less likely to be observed.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a meta-analysis conducted in the early 2000s revealed the association between reappraisal and physical health outcomes was nonsignificant; the exception was in the context of stressful circumstances that were uncontrollable (Penley et al, 2002). Other studies suggest reappraisal may be beneficial when stress exposure is high (e.g., among cancer survivors; Liao et al, 2017). However, no prior empirical support has been found for reappraisal as a significant contributor to physical health or well-being in a relatively healthy, low-stress population.…”
Section: A Brief Review Of Reappraisal and Healthmentioning
confidence: 99%
“…Although FCR research has been conducted hazardly in Western populations, few studies have been conducted with Chinese cancer patients or survivors, and of those they mostly investigated FCR itself and its association with quality of life 15‐19 . Only one study on Chinese cancer patients was identified in Hong Kong, which examined FCR and its association with meta‐cognition and neuroticism 19 .…”
Section: Introductionmentioning
confidence: 99%
“…The evidence for correlations between FCR and age, gender and physical symptoms is strongest, whereby younger patients, female patients and patients with more symptoms experience more FCR 6. In contrast, social support, optimism, having detailed information and being conscientious correlate with having less FCR 6 9 10. Notably, associations between FCR and psychological factors (eg, metacognitions) are generally stronger than associations between FCR and demographic factors 11.…”
Section: Introductionmentioning
confidence: 96%